2021
DOI: 10.1111/jmi.13075
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of Cu into the clinker phases

Abstract: The effect of CuO addition on the phase composition of clinker and the Cu incorporation into the structure of clinker phases was monitored under laboratory conditions. Separate synthesized CuO‐doped clinker phases as well as clinkers with different CuO content up to 4 wt.% were characterized by XRD, optical and electron microscopy with EDS analysis. It has been found that Cu tends to form a separate phase or a double oxide with Ca and incorporates in the clinker phases to a limited extent, except for C4AF. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…13,21 But mainly it forms a polluted double oxide together with Ca, which is consistent with Kolovos et al 9 However, Cu probably forms mainly submicroscopic inclusions of oxides in these phases, which can falsely affect the results of the SEM-EDS analysis. 18 This would also be confirmed by the results of X-ray analyses in Table 4. Electron microscopy results are consistent with the determined phase composition and light microscope observations.…”
Section: Designation Of Clinkersupporting
confidence: 65%
See 1 more Smart Citation
“…13,21 But mainly it forms a polluted double oxide together with Ca, which is consistent with Kolovos et al 9 However, Cu probably forms mainly submicroscopic inclusions of oxides in these phases, which can falsely affect the results of the SEM-EDS analysis. 18 This would also be confirmed by the results of X-ray analyses in Table 4. Electron microscopy results are consistent with the determined phase composition and light microscope observations.…”
Section: Designation Of Clinkersupporting
confidence: 65%
“…Recently, the entry of Cu into the clinker phases and the influence of CuO on clinker formation 18,19 and the influence of SO 3 in combination with individual selected cations (Cu, Mg and Li) on the properties of belite-rich clinker was studied. 20 Computer simulation techniques and theoretical calculations confirmed that Cu tends to replace mainly Fe atoms.…”
Section: Introductionmentioning
confidence: 99%
“…One of the current areas of cement research is lowenergy cements activated by various dopants or combinations of dopants. [10][11][12][13][14][15] The content and reactivity of C 4 AF changes significantly due to fluxes and mineralisers. A deeper understanding of the mobility of individual ions and compounds is needed to support recent knowledge of mechanisms of C 4 AF hydration.…”
Section: Introductionmentioning
confidence: 99%
“…The main components are quicklime, a source of SiO2 and various activators. As activators, Li and Cu were chosen, based on previous works [10,11], followed by KOH and sodium phosphate.…”
Section: Introductionmentioning
confidence: 99%